Odpowiedź :
Odpowiedź:
A.
[(2 1/2 - 1 2/3) : 1 1/9] * 1/12 = [(2 3/6 - 1 4/6) : 10/9] * 1/12 = [(1 9/6 - 1 4/6) * 9/10] * 1/12 = (5/6 * 9/10) * 1/12 = (1/2 * 3/2) * 1/12 = 3/4 * 1/12 = 1/16
B.
(1 1/3)² + [(2 5/8 - 1 3/4) : 1/2] = (4/3)² + [(2 5/8 - 1 6/8) * 2] =
= 16/9 + [(1 13/8 - 1 6/8) * 2] = 16/9 + (7/8 * 2) = 16/9 + 7/4 = 1 7/9 + 1 3/4 =
= 1 28/36 + 1 27/36 = 2 55/36 = 3 19/36
C.
(1 1/9 - 5/6) : (1 1/4 + 5/6) = (1 2/18 - 15/18) : (1 3/12 + 10/12) = (20/18 - 15/18) :
1 13/12 = 5/18 : 25/12 = 5/18 * 12/25 = 1/3 * 2/5 = 2/15
D.
(1 1/8 - 2/3) * 8/11 - (1/3)³ = (1 3/24 - 16/24) * 8/11 - 1/27 = (27/24 - 16/24) * 8/11 -
- 1/27 = 11/24 * 8/11 - 1/27 = 1/3 - 1/27 = 9/27 - 1/27 = 8/27
Szczegółowe wyjaśnienie: